How much is enough? Maintaining the biomechanical benefits of an ACL injury prevention training program - Weir, G.; Alderson, J.; Elliot, B.; Lee, S.; Donnelly, C. J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study investigated the effect of a 16-week maintenance training program which directly followed a high-dose 9 week initial training intervention, as part of a biomechanically informed ACL injury prevention program. Three-dimensional kinematic and kinetic data of elite female hockey players (n=16) were collected at baseline, post initial training and post maintenance training during unplanned sidestepping. Maintenance training was effective in retaining reduced peak knee valgus moments in a `high-risk` subgroup elicited from the initial training program. Conversely, although the total group demonstrated no benefits following initial training, they displayed a reduction (?-26.3%, g=0.30) in peak valgus knee moments following maintenance training, suggesting a prolonged albeit moderate dose of training was effective for this population.